Living as form socially engaged art from 1991-2011 - Thompson, Nato (Creative Time, 2012)
'Living as Form' grew out of a major exhibition at Creative Time in New York City. Like the exhibition, the book is a landmark survey of more than 100 projects selected by a 30-person curatorial advisory team; each project is documented by a selection of colour images.